PRAKTIK MANAJEMEN LABA SEBAGAI RESPON PENURUNAN TARIF PAJAK SESUAI UU NO. 36 TAHUN 2008, INSENTIF PAJAK, DAN NON INSENTIF PADA PERUSAHAAN YANG MASUK DALAM DAFTAR LQ 45 TAHUN 2009 DAN 2010 (Students' Journal of Accounting and Banking, 2015)
This research aims to find out whether the company doing the earnings managementas a response was to decrease income tax rates that occurred in 2008 by 30% to 28% in 2009 and 25% in 2010 and an additional intesif of 5% for companies that go public deposit 40% stake to the Indonesia Stock Exchange (IDX). The sample in this research are contained in the 42 companies at LQ 45’s list during the period 2009-2010. Methods of analysis used in this study is the difference t-test and multiple linear regression analysis. Test the difference t-test using one sample t-test to test whether there is a difference between the discretionary accrual thatsignificantbefore and after the decrease income tax rate. While, the multiple linear regression analysis was used to test whether tax incentives (tax planning) and non-tax incentives (earnings pressure, debt levels, earnings of bath, the size of the company, and the shares were deposited to IDX) affect the earnings management in responding to the decrase income tax rate. The results showed that in 2009 the company sample practice earnings management  by reducing profits to obtain larger tax savings. In addition, the company's earnings management practices in responding to the decrease in income tax rates are influenced by a non tax incentive. The non tax incentive are earnings pressure and earnings bath.Keywords: Decrase Income Tax Rate, Earnings Management, Tax Incentive, Non Tax Incentive